2023
DOI: 10.1001/jamanetworkopen.2023.11974
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Cognitive Deficits in Patients With Symptomatic SARS-CoV-2 and Their Association With Post–COVID-19 Condition

Abstract: ImportanceNeuropsychiatric symptoms are common in acute SARS-CoV-2 infection and in post–COVID-19 condition (PCC; colloquially known as long COVID), but the association between early presenting neuropsychiatric symptoms and PCC is unknown.ObjectiveTo describe the characteristics of patients with perceived cognitive deficits within the first 4 weeks of SARS-CoV-2 infection and the association of those deficits with PCC symptoms.Design, Setting, and ParticipantsThis prospective cohort study was conducted from Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…For example, the correlations between self-reports and performance-based cognitive measures tend to be weak to moderate in patients with depression, who often report more subjective cognitive complaints than what is revealed in performance-based measures ( Serra-Blasco et al, 2019 ; Douglas et al, 2018 ). Our exploratory analyses identified an association between symptoms of depression and posttraumatic stress and subjective cognitive complaints, supporting previous findings regarding COVID-19 patients ( Zlatar et al, 2017 ; Liu et al, 2023 ). Furthermore, depressive symptoms were found to be associated with scoring below the Mini-MoCA cut-off at six months.…”
Section: Discussionsupporting
confidence: 89%
“…For example, the correlations between self-reports and performance-based cognitive measures tend to be weak to moderate in patients with depression, who often report more subjective cognitive complaints than what is revealed in performance-based measures ( Serra-Blasco et al, 2019 ; Douglas et al, 2018 ). Our exploratory analyses identified an association between symptoms of depression and posttraumatic stress and subjective cognitive complaints, supporting previous findings regarding COVID-19 patients ( Zlatar et al, 2017 ; Liu et al, 2023 ). Furthermore, depressive symptoms were found to be associated with scoring below the Mini-MoCA cut-off at six months.…”
Section: Discussionsupporting
confidence: 89%
“…The second relevant finding of our study is represented by the higher sNfL and sGFAP levels in the eleven COVID-19 patients complaining of cognitive failures at T0. Cognitive deficits are common after COVID-19 and can impair executive functions, attention, and episodic memory 40 , 41 , 43 , 44 . Studies on the neuropsychological alterations during acute COVID-19 and in the post-COVID-19 phase show inhomogeneous results, particularly for the variable time of the evaluation, ranging from two to five weeks after the onset, up to one year after the recovery 42 , 43 , 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive deficits are common after COVID-19 and can impair executive functions, attention, and episodic memory 40 , 41 , 43 , 44 . Studies on the neuropsychological alterations during acute COVID-19 and in the post-COVID-19 phase show inhomogeneous results, particularly for the variable time of the evaluation, ranging from two to five weeks after the onset, up to one year after the recovery 42 , 43 , 45 , 46 . Most of these studies, however, mainly focus on hospitalized patients, being non-hospitalised patients somehow overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…216 Liu et al found that perception of (subjective) cognitive deficit during acute COVID-19 was associated with later Long-COVID, suggesting "an affective component to Post-COVID-19-condition in some patients." 217 Haddad et al found that "the number of moderate or severe persistent symptoms reported by individuals (in both an exposed uninfected group and an infected group) was associated with the number of moderate or severe persistent symptoms reported by their household members [i.e., prolonged symptoms tended to cluster within families]," and that "parents who reported their own health status at T1 was worse or much worse than before the pandemic were around 3-times more likely to report that their child had symptoms that persisted until T2." 23 The authors noted that in several other conditions, including chronic pain, CFS, and fatigue, "symptom measures in children are associated with parents' symptoms, stress, and/or parenting behavior."…”
Section: Source Quotationmentioning
confidence: 99%